EVALUATION OF BIOGAS YIELD AND MICROBIAL SPECIES FROM MULTI-BIOMASS FEEDSTOCKS (2014)
Virtually all countries, especially the developing nations, are being confronted with the twin problems of waste management and energy deficit. This development has led to the search for renewable energy sources. Although pig dung, water hyacinth and maize cob have been identified as good feedstocks for biogas production, studies utilising their mixtures have not been fully explored. This study was therefore designed to evaluate the biogas yield and microbial species from mixtures of biomass feedstocks. The feedstocks utilised for this study comprised Pig Dung (PD), Water Hyacinth (WH), and Maize Cob (MC). The PD and WH were sourced from University of Ibadan Teaching and Research Farm while MC was sourced from refuse bins in Oje Market. Six feedstock groups were selected namely PD, WH, MC, PD:MC (PM), PD:WH (PW), and PD:MC:WH (PMW). Each mixture was made in equal proportion on dry weight basis. A simple biogas digester was fabricated from a 10-litre plastic keg for feedstock biodegradation. Each feedstock sample to be digested was prepared by mixing 0.75 kg dry feedstock with 8.25 litres of water in the ratio of 1:11 (w/v) to form slurry. The slurry was fed into the corresponding digester, and kept for 35 days for anaerobic digestion while samples of the effluent were taken at seven days interval for five weeks for laboratory analyses. Parameters including temperature, pH, carbon, nitrogen, carbon to nitrogen (C-N) ratio, potassium, phosphorus, and microbial identification characteristics were determined using standard methods. Gas generated was estimated based on Archimedes’ Principle. Data were analyzed using descriptive statistics and ANOVA at p ˂ 0.05. Temperature and pH of all slurries ranged from 25.75±0.4oC to 28.75±0.4oC and 5.80±0.0 to 7.85±0.1 respectively. There was a significant difference in percentage nitrogen, phosphorus and potassium of the various slurries. Mean C-N ratio of the various slurries decreased from day 0 to day 35 as follows: 20.05±2.1 to 16.27±1.1, 23.28±0.1 to 12.95±1.2, 97.54±3.3 to 47.70±1.3, 57.27±0.2 to 28.34±2.1, 28.52±4.2 to 24.19±2.0 and 49.86±2.9 to 37.24±2.4 for PD, WH, MC, PM, PW, and PWM respectively. Predominant organisms identified at day 35 were: Methanobacterium, Enterobacter and Aspergillus spp. The anaerobic, coliform and fungal counts ranged from 6.80×102 to 1.0×105cfu/g, 4.3×104 to 6.2×106cfu/g, and 9.1×103 to 6.3×106cfu/g respectively throughout the duration of the study. The highest anaerobic count (1.0×105±0.03×105cfu/g) was recorded in PW on day 28. Peak biogas production was observed on day 23 for PD (987.50±3.5mL); day 24 for PW (1095.00±7.1mL), and PM (732.50±17.7mL); day 25 for MC (560.00±7.1mL), day 26 for WH (635.00±7.1mL) and PMW (662.50±10.6mL). Group PW had the highest biogas yield of 6067.00±38.2mL for the entire duration of the study. There was a significant difference between the mean biogas yields of the various feed stock groups. Co-digestion of pig dung with water hyacinth had the highest number of anaerobes and biogas yield as compared to single feed stocks. Therefore, the use of multi-biomass feed stocks for biogas production as a source of alternative energy production should be fully optimised.